The Effect of farmer chacteristics on entrepreneurial behavior of beekeepers in Kibwezi West Sub County, Makueni County - Strong, Margaret Mbesa (Strathmore University, 2021)
Agriculture plays a major role in the Kenyan economy through its significant contribution to the GDP, a foreign currency earner, supplier of raw materials to the processing and manufacturing sector as well as contributing to the food security in the country. In addition, the sector supports rural livelihoods through farm entrepreneurship and farm-generated employment thereby alleviating poverty levels in the rural population. Beekeeping is an important form of farming especially in the ASAL regions of the country where there are frequent occurrences of crop failure. The beekeeping subsector in Kenya is unable to satisfy the growing demand of honey in local, regional and global markets, producing 25 per cent of the national potential. The study sought to focus on beekeeping farmers and investigated their entrepreneurial behaviour, in that despite the huge market opportunity to commercialize their farm enterprises, the farmers operate at a subsistence level. The study aimed at establishing the effect of farmer characteristics on entrepreneurial behavior among bee farmers in Kibwezi West sub-county, Kenya. The study’s specific objective was to evaluate the effect of socio economics, psychological factors, group participation, and beekeeping management practices, on entrepreneurial behaviour of beekeeping farmers in Kibwezi West Sub County, Makueni County. The study was guided by the human capital entrepreneurship theory and the McClelland’s human motivation theory. The study applied descriptive research design. The study utilized purposive sampling technique to select 272 beekeepers from a target population of 816 beekeepers in Kibwezi West subcounty. Data was collected using a pretested questionnaire. The study realized a response rate of 83 per cent. The primary data collected was analyzed by applying descriptive and inferential statistical analysis utilizing SPSS statistical software. Data was presented using tables. Regression results indicated that age, education, number of beehives, psychological factors, and extension participation, had a positive and significant effect on entrepreneurial behaviour. Psychological factors and extension participation had high significant influence on entrepreneurial behaviour whereas age, education and number of beehives had a marginal effect. The beekeeping farmers were found to have moderate entrepreneurial behaviour. The study therefore recommends that entrepreneurship development programs targeting beekeepers should prioritize the enhancement of psychological motivation levels of beekeepers namely economic motivation and market orientation, through training and market linkages. In addition, more opportunities for extension participation should be provided, specifically through peer learning via farm visits and practical demonstration of beekeeping management practices – these factors were associated with higher farmer extension participation.
A dissertation submitted in partial fulfillment for the award of the degree of Master of Management in Agribusiness, Strathmore University
Keywords: Farmer Characteristics; Entrepreneurship Behaviour; Beekeeping